Comparative Evaluation of Anti-HER2 Affibody Molecules Labeled with Cu-64 Using NOTA and NODAGA - Vladimir Tolmachev; Cheng-Bin Yim; Johan Rajander; Anna Perols; Amelie Eriksson Karlström; Merja Haaparanta-Solin; Tove J. Grönroos; Olof Solin; Anna Orlova (WILEY-HINDAWI, 2022)
Imaging using affi body molecules enables discrimination between breast cancer metastases with high and low expression of HER2, making appropriate therapy selection possible. This study aimed to evaluate if the longer half-life of Cu-64 (T-1/2 = 12.7h) would make Cu-64 a superior nuclide compared to Ga-68 for PET imaging of HER2 expression using affibody molecules. The synthetic ZHER2: S1 affibody molecule was conjugated with the chelators NOTA or NODAGA and labeled with Cu-64. The tumor-targeting properties of Cu-64-NOTA-ZHER2: S1 and Cu-64-NODAGA-ZHER2: S1 were evaluated and compared with the targeting properties of Ga-68-NODAGA-ZHER2: S1 in mice. Both 64 Cu-NOTA-ZHER2: S1 and Cu-64-NODAGA-ZHER2: S1 demonstrated specific targeting of HER2-expressing xenografts. At 2 h after injection of Cu-64-NOTA-ZHER2: S1, Cu-64-NODAGA-ZHER2: S1, and Ga-68-NODAGAZHER2: S1, tumor uptakes did not differ significantly. Renal uptake of Cu-64-labeled conjugateswas dramatically reduced at 6 and 24 h after injection. Notably, radioactivity uptake concomitantly increased in blood, lung, liver, spleen, and intestines, which resulted in decreased tumor-to-organ ratios compared to 2 h postinjection. Organ uptake was lower for Cu-64-NODAGA-ZHER2: S1. The most probable explanation for this biodistribution pattern was the release and redistribution of renal radiometabolites. In conclusion, monoamide derivatives of NOTA and NODAGA may be suboptimal chelators for radiocopper labeling of anti-HER2 affibody molecules and, possibly, other scaffold proteins with high renal uptake.